The concept of the network society of M. Castells - Nadezhda Evgenievna Serkina (Вестник Майкопского государственного технологического университета)
The novelty of the research consists in the need for a theoretical analysis of large-scale changes that occur in modern society under the influence of the rapid development of information and communication technologies. Social changes are reflected by scientists in the framework of the concepts of “information”, “post-industrial”, “technotronic”, etc. society, and each author identifies his own reasons for the genesis and main features of the current stage of development of Western technological civilization, which represents a certain problem of its social and humanitarian knowledge. The purpose of the research is to analyze the influence of information technologies on the main social subsystems within the framework of a civilizational approach to the development of Western European civilization using the results of the original research of M. Castells, dedicated to the idea of a network society, In the article the author considered the features of information technology revolution of the last third of the XX century which had changed the shape of industrialized countries of the West. In his research he relied upon the principles of determinism and historicism, and the idea of technogenic civilization, according to which the decisive role in the mechanism of social determination of modern society belonged to its production subsystem, which, through various mediating links, determined the state of other spheres of society. He also the consequences of the revolution for all social spheres of technogenic societies, including the formation of a global information economy, a social structure of a network society, and “real virtuality” culture. It has been concluded that network structures in the post-industrial economy become the basis for the sustainable development of all public spheres, allowing to combine high rates of social development and sustainability of basic social institutions.